Pembelajaran Berbasis Case Method untuk Meningkatkan Kemampuan Pemecahan Masalah Mahasiswa PGSD - Maxsel Koro (FONDATIA, 2023)
The ability to solve problems is an important thing to teach students. This is because, in real life, every individual faces various problems that need to be faced and resolved. This research was conducted with the aim of increasing students' ability to solve problems in the Global Perspective Course with the Topic: The Influence of Science and Technology in Human Life. The research method used is Classroom Action Research which includes: planning, implementing action, observation, and reflection. Before the action is taken, the initial data on student abilities are recorded by giving an initial test (pretest). This study's results indicate an increase in students' ability to solve problems in the Global Perspective Course. It can be seen from the difference in the results of problem-solving abilities in the pre-cycle, cycle one, and cycle two which continued to increase where in the second cycle 80%, namely 92.1% (35 students) were able to solve problems well and scored above the completeness standard. There is an increase in the activity of lecturers and students from cycle I to cycle II, which is above 80%.